2010
DOI: 10.1158/1940-6207.capr-09-0068
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Phosphate Activates N-ras and Promotes Cell Transformation and Skin Tumorigenesis

Abstract: Recent results suggest a paradigm shift from viewing inorganic phosphate as a passive requirement for basic cell functions to an active regulator of cell behavior. We have previously shown that elevated concentrations of phosphate increased cell proliferation and expression of protumorigenic genes such as Fra-1 and osteopontin in a preosteoblast cell line. Therefore, we hypothesized that elevated phosphate concentrations would promote cell transformation in vitro and tumorigenesis in vivo. Supplementation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 60 publications
0
83
0
Order By: Relevance
“…RAS genes are related to cellular responses such as proliferation, cell cycle and apoptosis (Malumbres and Pellicer, 1998). Moreover, in a mouse model of skin carcinogenesis, high doses of dietary phosphate (1.2%) significantly enhanced the skin papilloma number through an increase in the circulating OPN levels (Camalier et al, 2010).…”
Section: Influence Of Pi On Cellular Signaling and Tumorigenesismentioning
confidence: 96%
See 1 more Smart Citation
“…RAS genes are related to cellular responses such as proliferation, cell cycle and apoptosis (Malumbres and Pellicer, 1998). Moreover, in a mouse model of skin carcinogenesis, high doses of dietary phosphate (1.2%) significantly enhanced the skin papilloma number through an increase in the circulating OPN levels (Camalier et al, 2010).…”
Section: Influence Of Pi On Cellular Signaling and Tumorigenesismentioning
confidence: 96%
“…Increased levels of Pi also activate signaling pathways involving the neuroblastoma RAS viral oncogene homolog (N-ras) (Camalier et al, 2010). Ras genes are oncogenes that are activated in cancer.…”
Section: Influence Of Pi On Cellular Signaling and Tumorigenesismentioning
confidence: 99%
“…These results agreed with Brada el al [46] and disagreed with Kristensen et al [47] as survival was found to be inversely associated with serum ionized calcium levels. It was found that elevated levels of phosphorus were necessary for adequate growth of some types of cancers [6], [7]. This rise in phosphorus is due to heightened requirements of protein synthesis needed during accelerated cell growth [8].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of serum Pi were found to modify gene expression as well as protein translation and affect the rate of cell proliferation in vitro [4], [5]. Moreover, a high Pi in a diet has been reported to result in a significantly increased development of lung and skin cancers, as well as perturbed normal brain growth in animal studies [6], [7], which denoted the potential link between Pi and carcinogenesis in humans. In the human body, Pi is known to be mainly regulated by a set of hormonal and metabolic factors, which tightly control calcium homeostasis, i.e.…”
Section: Introductionmentioning
confidence: 97%
“…A study by Camalier et al (2010) investigated the effects of evaluated levels of inorganic phosphate on cell proliferation and anchorage-independent growth of transformed epidermal cell line JB6 and mice skin tumorigenesis. Their results indicated that an increase in the level of P i in the cell culture medium promoted cell proliferation and skin tumorigenesis by, in part, increasing the availability of phosphate for activation of N-ras and its downstream targets, ERK1/2, activator protein-1, as well as increased gene expression of Fra-1, COX-2, and osteopontin in a dosedependent manner.…”
Section: Sponge Cell Exposure To Inorganic Phosphatementioning
confidence: 99%